Recognition of specified RNA modifications by the innate immune system - Eigenbrod, Tatjana; Keller, Patrick; Kaiser, Steffen; Rimbach, Katharina; Dalpke, Alexander; Helm, Mark (RNA modification, 2015)
Microbial nucleic acids have been described as important activators of human innate immune responses by triggering so-called pattern recognition receptors (PRRs) that are expressed on innate immune cells, including plasmacytoid dendritic cells and monocytes. Although host and microbial nucleic acids share pronounced chemical and structural similarities, they significantly differ in their posttranscriptional modification profile, allowing the host to discriminate between self and nonself. In this regard, ribose 2′-O-methylation has been discovered as suppressor of RNA-induced PRR activation. Although 2′-O-methylation occurs with higher frequencies in eukaryotic than in prokaryotic RNA, the immunosuppressive properties of 2′-O-methylated nucleotides may be misused by certain bacteria as immune evasion mechanism. In the course of identifying inhibitory RNA modifications, our groups have synthesized and comparatively analyzed a series of differentially modified RNAs, so-called modivariants, for their immune stimulatory capacities. In this chapter, we will detail the protocols for the design and synthesis of RNA modivariants by molecular cut-and-paste techniques (referred to as molecular surgery) and describe testing of their immune stimulatory properties upon transfection into peripheral blood mononuclear cells.